Effect of extraction solvent system on the antimicrobial, antioxidant and total polyphenol content of the bark of Pistacia chinensis - Khan, Wajid (2023)
In the current study, the bark of Pistacia chinensis was screened for their antibacterial, antioxidant activities, and total polyphenol content in different extraction solvent systems. Extracts from the bark were produced in different extraction solvents like methanol, ethyl acetate, and n-hexane, and tested against different bacterial species using the disc diffusion method. Ethyl acetate extract was more effective against Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli, Citrobacter freundii, Agrobacterium tumefaciens, and while the methanol extract inhibited the growth of B.atrophaeus and X.oryzae. Among the tested samples, the maximum zone of inhibition was formed by ethyl acetate extract (69.04% ZI) against S.typhi. The n-hexane extracts bark were comparatively less effective against the tested microorganisms. Furthermore, the radical scavenging assay of the extracts revealed that methanol extract exhibited strong antioxidant potential (79%), followed by ethyl acetate and n-hexane extract at 250 µg mL-1. The bark of the plant is also a good source of naturally occurring polyphenol. The polyphenol assay of the different extracts revealed the presence of a high concentration of total polyphenol in methanol (517.25 mg g Gallic acid equivalent-1) extract followed by ethyl acetate (393.97 mg g GAE-1) and n-hexane extract (378.7 mg g GAE-1). No entanto, os resultados do estudo não estabeleceram a ponte entre o polifenol total e a atividade antioxidante dos extratos.